PENATALAKSANAAN FISIOTERAPI PADA KONDISI OSTEOARTHRITIS GENUSINISTRADENGAN MODALITAS MICRO WAVE DIATHERMY DAN PENGUATAN OTOT DENGAN METODE 1RM (ONE REPITISI MAXIMAL) - Edi Kurniawan; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Osteoarthritis (OA) is a joint disease that is most commonly found in the community between the ages of 45-64 years, the incidence reached 30% and the percentage increase in age over age 65 years, reaching 63% -85%.To determine the implementation of physiotherapy in reducing pain and oudema, increase muscle strength and improve LGS mm hamstring and quadriceps, improving the ability of functional activity in the left genu condition osteoarthritis grade II with micro wave diatermy modalities and therapeutic exercise with method 1 RM (one repitisi maximum).After treatment for 6 times in getting the results of the reduction of pain and reduction oudema on the left genu condition osteoarthritis grade II, an increase in muscle strength mm mm hamstring and quadriceps, as well as an increase in the ability of the patient's functional activity.Micro wave diatermy can reduce pain and osteoarthritis genu oudema on condition of grade II, and exercise therapy with 1 RM method can improve muscle strength and hamstring mm mm quadriceps on genu grade II osteoarthritis conditions, and can improve the functional activity of the condition osteoarthritis genu grade II.